2019
DOI: 10.1152/jn.00083.2019
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the subjective visual vertical during sustained optokinetic and galvanic vestibular stimulation

Abstract: The brain is thought to use rotation cues from both the vestibular and optokinetic system to disambiguate the gravito-inertial force, as measured by the otoliths, into components of linear acceleration and gravity direction relative to the head. Hence, when the head is stationary and upright, an erroneous percept of tilt arises during optokinetic roll stimulation (OKS) or when an artificial canal-like signal is delivered by means of galvanic vestibular stimulation (GVS). It is still unknown how this percept is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Note that tilt signals have been identified in the navigation system (Angelaki et al, 2020), but these cells were not tested during tilt/translation discrimination protocols, thus it is unknown whether they convey a net tilt signal. Although tilt perception is driven by a 3D internal model in humans (Clark & Graybiel, 1966; Merfeld et al, 2001; Niehof et al, 2019a, 2019b; Vingerhoets et al, 2007), whether tilt-selective cells exist outside the NU remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that tilt signals have been identified in the navigation system (Angelaki et al, 2020), but these cells were not tested during tilt/translation discrimination protocols, thus it is unknown whether they convey a net tilt signal. Although tilt perception is driven by a 3D internal model in humans (Clark & Graybiel, 1966; Merfeld et al, 2001; Niehof et al, 2019a, 2019b; Vingerhoets et al, 2007), whether tilt-selective cells exist outside the NU remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although tilt perception is driven by a 3D internal model in humans (Clark & Graybiel, 1966;Merfeld et al, 2001;Niehof et al, 2019aNiehof et al, , 2019bVingerhoets et al, 2007), whether tilt-selective cells exist outside the NU remains unknown.…”
Section: Neuronal and Behavioural Outputs Of The Numentioning
confidence: 99%
“…10 healthy participants (4 male and 6 female between the ages of [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] with no known history of neurological disease or injury participated in this study. Prior to participation, the experimental protocol was explained and participant's informed written consent obtained.…”
Section: Participantsmentioning
confidence: 99%
“…Theory predicts that by combining cues in this manner, the brain can achieve a statistically optimal inference such that its variance is minimized [21,22]. Near optimal combination of visual and vestibular motion signals has been observed during translational self-motion perception [23], (For review see: [24,25]) and has been used successfully to model visual and vestibular interactions during angular motion [26][27][28], suggesting the brain may indeed achieve an optimal internal representation of the angular velocity of the head through a variance based weighting scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The direction of gravity cannot be directly sensed; instead, it is estimated in the brain based on several types of sensory information. Numerous psychophysical studies have demonstrated the involvement of visual [1][2][3], somatosensory [4][5][6], and vestibular sensory signals [3,7] in estimates of gravitational direction. Moreover, recent studies using computational modeling have shown that the central nervous system (CNS) weighs and combines these multisensory signals with prior knowledge and experience about the earth-vertical direction in a statistically optimal manner to resolve sensory ambiguity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%